Das águas do rio, as mulheres em movimento na defesa do Xingu: a resistência contra a construção da hidrelétrica de Belo Monte em Altamira - Oeste do Pará - PAIVA, Angela Maria Trindade (Universidade Federal do Pará, 2014)
The complex issues surrounding the conflicts in the construction of hydroelectric dam involving, on the one hand, the Brazilian Electric Sector, and on the other, segments of society such as indigenous peoples, “traditional populations”, riverside living, fishermen and also the populations of urban areas, among others, have been recurrent in the last few decades. To some extent, we can indicate that such conflicts arise from different and contradictory ways in which these segments of society see, experience and use the nature and their environment. Motivated by the interest of deepening the analysis on these conflicts in the Amazon region, and expand my knowledge, sustained by the interpretative matrix of making and anthropological thinking, underpin the development of this work focusing on the dialogue with twelve women who acts as a group articulated in defense of the Xingu’s river and therefore against the Belo Monte hydroelectric dam, scheduled to be built in the western state of Para. To this group of "Women of the Xingu" the building of the hydroelectric dam will bring environmental and social impacts, that they understand as detrimental to the entire region, but especially for women who lives in that region. In this sense, we wish to understand the peculiarities that elapse from this way of seeing and the meaning of world which leads these women to do this reading and articulated political acts in defense of the nature.